ChemInform Abstract: Rhodium(III)‐Catalyzed Direct Cyanation of Aromatic C—H Bond to Form 2‐(Alkylamino)benzonitriles Using N‐Nitroso as Directing Group. Issue 18 (April 2016) - Dong, Jiawei; Wu, Zhongjie; Liu, Zhengyi; Liu, Ping; Sun, Peipei
Abstract: Using N‐tosyl‐N‐cyanoaniline as CN source, the Rh‐catalyzed cyanation of N‐alkyl‐N‐nitroso‐anilines proceeds in modest to high yields.